Evaluation of Extension Contact of Apple Growers for Recommended Apple Production Technology - Shah, Zahoor Ahmad; Dar, Mushtaq Ahmad; Wani, Noor Ul Islam; Maqbool, Showkat; Dar, Eajaz Ahmad (Indian Journal of Extension Education, 2021)
Innovative techniques and technologies are being developed at different research stations for the enhancement of apple production. But due to poor extension contact with credible agencies, the same technology has not been fully utilised by the growers at their farms. The study was conducted in three districts of Kashmir division selected purposively with multistage sampling; having maximum area under apple cultivation. The study used focus group discussions, key informant interviews, and a household survey. The majority of the apple growers from district Shopian (55.44%) and district Baramulla (48.67%) were having medium level of extension contact with different extension agencies in contrast to district Budgam, where majority of the apple growers were having low level of extension contact. However, majority of the apple growers from district Shopian (61.39%) contacted private agencies for consultation, while high level of contact (48.81% of apple growers) with private agencies was found among the apple growers of district Budgam.
Keywords: Apple; Extension contact; Evaluation; Growers; Technology